effect of some adenosine componunds on smooth muscles of the sheep bladder osteius ovis L - al-aANI, Fakher S.; Mohammed, S. M.; AL-Ani, iqbal N. (Journal of the Faculty of Medicine Baghdad, 2006)
Background: